Silicon-carbon composite negative electrode material, application, preparation method and preparation system
Through the preparation process of the silicon-carbon composite negative electrode material preparation system, the problem of volume expansion of the silicon-carbon composite negative electrode material during charging and discharging is solved, and efficient cycling performance and safety improvement is achieved.
Patent Information
- Application Number
- CN201911349017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2039-12-24
AI Technical Summary
The volume expansion of silicon-carbon composite anode material during charging and discharging is severe, resulting in material powderization, electrode fragment fracture and lithium ion moving channels, affecting battery life and safety.
A silicon-carbon composite negative electrode material preparation system is adopted, including a mixer, a static mixer, a pelletizer and a high-temperature carbonization furnace. Through the steps of initial mixing, remixing, pelletizing and high-temperature carbonization, powdered silicon-carbon composite negative electrode material is prepared.
It effectively reduces the volume expansion of silicon, improves the circulation performance of the material, improves the reversible specific capacity and charge and discharge efficiency of the negative electrode material, extends the cycle life of the battery and improves safety.
Smart Images

Figure CN113036224B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery negative electrode materials, and specifically relates to a silicon-carbon composite negative electrode material, application, preparation method and preparation system. Background Art
[0002] Lithium-ion batteries are widely used as mainstream power sources in mobile communication devices and 3C electronic products due to their small size, high energy density, high voltage, and no memory effect. In recent years, electric vehicles, which have emerged worldwide due to environmental pollution and energy crisis, also use lithium-ion batteries as energy storage devices. At present, the capacity of secondary batteries in traditional lithium cobalt oxide / graphite, lithium iron phosphate / graphite systems is close to its theoretical capacity limit, and it is difficult to increase its energy density by increasing the dressing density, thinning the current collector or the thickness of the diaphragm.
[0003] At present, the negative electrode materials of commercial lithium-ion batteries are still mainly traditional graphite negative electrode materials. The actual specific capacity is close to the theoretical value of 372mAh / g. It is very difficult to improve it. If you want to improve the energy density, combining it with silicon is a better way. Asphalt has the advantages of abundant resources, low price, high carbon content and easy graphitization. Asphalt as one of the forms of carbon source has become a hot topic at present. Silicon has the highest specific capacity (4200mAh / g) and a moderate voltage platform (~0.4V vs Li / Li+). Its theoretical specific capacity is much higher than that of graphite. Silicon is currently known to have the highest theoretical specific capacity for negative electrode materials. In addition, due to the advantages of silicon materials such as environmental friendliness, abundant reserves and low cost, it has become the focus of current research and development. However, in the actual use process, there are many inherent "deficiencies" in silicon-carbon negative electrodes.
[0004] The main problem is volume expansion. During the charge and discharge process, the volume of silicon will expand by 100%-300%. The continuous contraction and expansion will cause the silicon-carbon negative electrode material to become powdery, seriously affecting the battery life; secondly, the continuous expansion of silicon will generate a lot of stress inside the lithium-ion battery. This stress will squeeze the pole piece, and the pole piece may break after multiple cycles; thirdly, due to the internal stress of the lithium-ion battery, it is very likely to cause the internal porosity of the lithium-ion battery to decrease, reduce the lithium ion movement channel, cause the precipitation of lithium metal, and affect the battery safety. For this reason, silicon-carbon composite negative electrode materials face high technical barriers in research and development and application. Summary of the invention
[0005] In view of the above-mentioned shortcomings or deficiencies of the prior art, the technical problem to be solved by the present application is to provide a silicon-carbon composite negative electrode material, application, preparation method and preparation system.
[0006] To solve the above technical problems, this application is implemented through the following technical solutions:
[0007] The present application proposes a silicon-carbon composite negative electrode material preparation system, the preparation system comprising:
[0008] Mixer, add silica powder and asphalt in a certain proportion and mix them initially;
[0009] Static mixer, the premixed mixture enters the static mixer for further mixing;
[0010] A pelletizer, wherein the mixture mixed by the static mixer enters the pelletizer for pelletizing and crushing;
[0011] and a high-temperature carbonization furnace. After the granulation and crushing treatment, the mixture enters the high-temperature carbonization furnace for high-temperature carbonization treatment to obtain a powdered silicon-carbon composite negative electrode material.
[0012] Furthermore, the above-mentioned preparation system further includes a turbulator, which is arranged at the outlet end of the static mixer, and the mixture processed by the static mixer is again processed by the turbulator for homogenization and dispersion.
[0013] Furthermore, in the above-mentioned preparation system, the turbulator includes a plurality of layers of perforated plates, wherein the holes on each layer of the perforated plates are arranged in a non-uniform and disordered state.
[0014] Furthermore, in the above-mentioned preparation system, the pore size range of the perforated plate is between 5 μm and 8 mm.
[0015] Furthermore, the above-mentioned preparation system further includes a water tank, which is arranged at the outlet end of the static mixer, and the mixture after exiting the static mixer enters the water tank for cooling treatment.
[0016] Furthermore, the above-mentioned preparation system further includes a blow dryer, which is arranged at the outlet end of the water tank. After the mixture is cooled in the water tank, it enters the blow dryer to dry the moisture on its surface.
[0017] Furthermore, the above-mentioned preparation system further includes a vibrating screen, which is arranged at the outlet end of the pelletizer. The mixture processed by the pelletizer is processed by a vibrator and then screened for mixture particles within a certain particle size range.
[0018] Furthermore, in the above-mentioned preparation system, the mixture particles are cylindrical particles.
[0019] Furthermore, in the above-mentioned preparation system, the diameter of the mixture particles is 3-5 nm and the length is 5-8 nm.
[0020] Furthermore, the above-mentioned preparation system further includes a feeder, in which at least two feeding bins are configured, and the silicon powder and the asphalt enter the mixer through the corresponding feeding bins for initial mixing.
[0021] Furthermore, in the above-mentioned preparation system, the feeder includes one of a loss-in-weight feeder, a high-speed mixer and an internal mixer.
[0022] Furthermore, in the above-mentioned preparation system, tin powder is added to one of the feeding bins, and the mass percentage of the tin powder to the silicon powder is 10-20%.
[0023] Furthermore, in the above-mentioned preparation system, boron powder is added to one of the feeding bins, and the mass percentage of the boron powder to the silicon powder is 1-2%.
[0024] Furthermore, in the above-mentioned preparation system, a surface coupling agent is added into one of the feeding bins.
[0025] Furthermore, in the above-mentioned preparation system, the mass percentage of the silicon powder and the asphalt is between 5-10%.
[0026] Furthermore, in the above-mentioned preparation system, the mixer includes one of a twin-screw extruder, a single-screw extruder, and a reciprocating worm extruder.
[0027] The present application also proposes a method for preparing a silicon-carbon composite negative electrode material, the preparation method comprising the following steps:
[0028] Add asphalt and silica fume in a certain proportion and perform initial mixing;
[0029] Remixing the above mixture;
[0030] The remixed mixture is pelletized;
[0031] The mixture after the cutting process is subjected to high-temperature carbonization treatment to obtain a silicon-carbon composite negative electrode material.
[0032] Furthermore, in the above-mentioned preparation method, a feeding process is also included before the initial mixing process, and the feeding process adopts one of a loss-in-weight feeder, a high-speed mixer and an internal mixer for feeding.
[0033] Furthermore, in the above-mentioned preparation method, the feeding process further comprises adding tin powder through one of the feeding bins, wherein the mass percentage of the tin powder to the silicon powder is 10-20%.
[0034] Furthermore, in the above-mentioned preparation method, the feeding process further comprises adding boron powder through one of the feeding bins, wherein the mass percentage of the boron powder to the silicon powder is 1-2%.
[0035] Furthermore, in the above-mentioned preparation method, the feeding process also includes adding a surface coupling agent through one of the feeding bins.
[0036] Furthermore, in the above-mentioned preparation method, the mass percentage of the silicon powder and the asphalt is between 5-10%.
[0037] Furthermore, in the above-mentioned preparation method, the initial mixing process comprises: using one of a twin-screw extruder, a single-screw extruder, and a reciprocating worm extruder to perform a blending extrusion process.
[0038] Furthermore, in the above-mentioned preparation method, the process of remixing the above-mentioned mixture includes: remixing the above-mentioned mixture using a static mixer.
[0039] Furthermore, in the above-mentioned preparation method, a turbulent blending process is further included before the pelletizing process, and the mixture is homogenized and dispersed by the turbulent blending process.
[0040] Furthermore, in the above-mentioned preparation method, the turbulent blending treatment process adopts the turbulator to perform turbulent blending treatment, wherein the turbulator includes a multi-layered perforated plate, and the holes on each layer of the perforated plate are arranged in a non-uniform and disordered state.
[0041] Furthermore, in the above-mentioned preparation method, the pore size range of the perforated plate is between 5 μm and 8 mm.
[0042] Furthermore, the above-mentioned preparation method further includes a cooling treatment, wherein the mixture is cooled after the re-mixing treatment, wherein the cooling treatment includes water cooling treatment using a water tank or air cooling treatment.
[0043] Furthermore, the above-mentioned preparation method further includes a drying process, wherein after the mixture is cooled by the above-mentioned water, the moisture on the surface of the mixture is dried by blowing.
[0044] Furthermore, in the above-mentioned preparation method, the mixture after pelletizing is cylindrical particles.
[0045] Furthermore, in the above preparation method, the diameter of the cylindrical particles is 3-5 mm and the length is 5-8 mm.
[0046] Furthermore, the above-mentioned preparation method further includes a vibration screening process, wherein the mixture after the pelletizing process is subjected to the vibration screening process to screen the mixture particles within a certain particle size range.
[0047] The present application also proposes a silicon-carbon composite negative electrode material, which is obtained by the above-mentioned preparation method.
[0048] The present application also proposes an application of a silicon-carbon composite negative electrode material, including the application of the silicon-carbon composite negative electrode material obtained by the above-mentioned preparation method in a negative electrode plate.
[0049] Furthermore, in the application of the above silicon-carbon composite negative electrode material, the silicon-carbon composite negative electrode material is evenly coated on the surface of a substrate to obtain a pole piece.
[0050] Compared with the prior art, this application has the following technical effects:
[0051] The reversible specific capacity of the silicon-carbon composite negative electrode material of the present application is greater than 820 mAh / g, and the first charge and discharge efficiency is greater than 84.5%. The present application effectively reduces the volume expansion of silicon and maintains the high conductivity of the silicon-carbon composite negative electrode material, greatly improving the material cycle performance; the silicon-carbon composite negative electrode material of the present application has the characteristics of high capacity, long cycle life and high conductivity; the preparation process of the present application is simple and easy to control, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:
[0053] Figure 1 : Schematic diagram of the overall structure of the silicon-carbon composite negative electrode material preparation system of the present application;
[0054] Figure 2 : Process flow chart of the method for preparing the silicon-carbon composite negative electrode material of the present application;
[0055] Figure 3 : A graph showing the change in capacitance of the silicon-carbon composite negative electrode material during charge and discharge. DETAILED DESCRIPTION
[0056] The concept, specific structure and technical effects of the present application will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present application.
[0057] like Figure 1As shown, the silicon-carbon composite negative electrode material preparation system of this embodiment includes: a mixer 10, a static mixer 20, a pelletizer 50 and a high-temperature carbonization furnace, wherein the mixer 10 adds silicon powder and asphalt in a certain proportion and performs preliminary mixing; the mixture after the above premixing enters the static mixer 20 for further mixing; the mixture mixed by the above static mixer 20 enters the pelletizer 50 for pelletizing and fragmentation; the mixture after pelletizing and fragmentation enters the high-temperature carbonization furnace for high-temperature carbonization to obtain a powdered silicon-carbon composite negative electrode material. The dispersed silicon-carbon composite negative electrode material of this embodiment includes mixing silicon powder with materials of different materials (such as asphalt, etc.), covering a highly uniformly dispersed composite system in which silicon and carbon elements form molecular contact. In this embodiment, the silicon powder is uniformly dispersed in a carbon buffer matrix (such as asphalt), which can inhibit the volume expansion of silicon to a certain extent, thereby avoiding the cycle life and safety problems caused by volume expansion.
[0058] In this embodiment, the particle size of the silicon powder does not exceed 200-300nm. Furthermore, in order to further reduce the safety hazard and service life problems caused by the volume expansion of silicon, the particle size of the silicon powder is preferably 40-250nm; further, preferably 40-200nm; further, preferably 40-180nm; further, preferably 40-150nm; further, preferably 40-120nm; further, preferably 40-100nm; further, preferably 40-90nm; further, preferably 40-80nm; further, preferably 40-70nm; further, preferably 40-60nm; further, preferably 40-50nm.
[0059] In this embodiment, the mixer 10 is further equipped with a driving motor 101 .
[0060] This embodiment also includes a feeder, in which at least two feeding bins 11 are configured, and the silicon powder and the asphalt enter the mixer 10 through the corresponding feeding bins 11 for initial mixing.
[0061] The feeder includes a weightless feeder, a high-speed mixer and an internal mixer. Of course, other methods can be used for feeding, such as using an atomizing sprayer to continue atomizing and spraying feeding, using a high-speed mixed flow homogenizing device for feeding, and using an ultrasonic oscillator for feeding. The above feeding methods are only examples and do not limit the scope of protection of this application.
[0062] Among them, in this embodiment, in order to obtain a better silicon-carbon composite effect and to suppress the volume expansion of silicon to a certain extent, the mass percentage of the silicon powder and the asphalt is preferably between 5-10%; further, preferably 5-9%; further, preferably 5-8%; further, preferably 5-7%; further, preferably 5-6%.
[0063] Furthermore, when the asphalt and silicon powder are added as above, tin powder can also be added through one of the feeding bins 11, and the mass percentage of the tin powder to the silicon powder is 10-20%; further, preferably 11-19%; further, preferably 12-18%; further, preferably 13-17%; further, preferably 14-15%.
[0064] Furthermore, in the process of adding asphalt and silicon powder, or in the process of adding asphalt, silicon powder and tin powder, boron powder can also be added through one of the feeding bins 11, and the mass percentage of the boron powder to the silicon powder is 1-2%; further, preferably 1-1.5%.
[0065] In order to further promote the dispersion of the material and avoid excessive oxidation of the silicon powder, a surface coupling agent may be added through one of the feeding bins 11, wherein the surface coupling agent may be made of existing materials.
[0066] In this embodiment, the mixer includes one of a twin-screw extruder, a single-screw extruder, and a reciprocating worm extruder. In this embodiment, the mixing process is carried out by extrusion, so that the mixture is mixed more uniformly and has a higher degree of dispersion.
[0067] The static mixer 20 utilizes a mixing unit fixed in the tube to change the flow state of the mixture in the tube, so that two or more fluids are cut, sheared, rotated and remixed, thereby achieving good dispersion and sufficient mixing between the fluids.
[0068] Furthermore, this embodiment further comprises a turbulator (not shown in the figure), which is arranged at the outlet end of the static mixer 20, and the mixture processed by the static mixer 20 is again processed by the turbulator for homogenization and dispersion.
[0069] Wherein, the turbulator includes a plurality of layers of perforated plates, and the holes on each layer of the perforated plates are arranged in a non-uniform and disordered state. In this embodiment, the shape of the holes on the perforated plates is not limited, and can be one or more of circular holes, elliptical holes, square holes, petal-shaped holes, etc. Of course, for the convenience of processing and manufacturing, holes of the same shape with different aperture sizes can also be used, wherein, in order to obtain a better homogenization and dispersion effect, the holes with different aperture sizes are arranged in a non-uniform, disordered or irregular manner.
[0070] Preferably, the holes of the upper and lower perforated plates are staggered with each other, and smaller holes are formed by superposition of the upper and lower perforated plates to further enhance the homogenization and dispersion effect.
[0071] Furthermore, the number of layers of the perforated plates can be appropriately increased or decreased according to actual usage. Of course, if the number of perforated plates is greater, the homogenization and dispersion effect of the mixture may be better, but the energy consumption will increase to a certain extent.
[0072] In this embodiment, the pore size range of the perforated plate is preferably between 5 μm and 8 mm.
[0073] Furthermore, the present embodiment further comprises a water tank 30, which is arranged at the outlet end of the static mixer 20, and the mixture after exiting the static mixer 20 enters the water tank 30 for cooling treatment. Since the overall temperature of the mixture will rise after the mixing treatment in the static mixer 20, in order to avoid the influence of the subsequent equipment due to the excessive temperature, in the present embodiment, the mixture is cooled by adding the water tank 30.
[0074] Among them, the above-mentioned water cooling treatment can also be replaced by air cooling treatment, and the air cooling treatment can also achieve the technical effect of cooling down the mixture.
[0075] Since the mixture is cooled by the water tank 30, water is attached to the surface of the mixture. The present embodiment is further provided with a blow dryer 40, which is arranged at the outlet end of the water tank 30. After the mixture is cooled by the water tank 30, it enters the blow dryer 40 to dry the moisture on its surface.
[0076] In this embodiment, the mixture after pelletizing by the pelletizer 50 is preferably cylindrical particles, and further, the diameter of the mixture particles is 3-5 mm and the length is 5-8 mm. The data range listed above is a preferred range. Of course, there may be mixture particles that are not within the preferred range during the pelletizing process. Therefore, this embodiment further screens and selects through the vibration screen 60 described below.
[0077] This embodiment further includes a vibrating screen 60, which is disposed at the outlet of the pelletizer 50. The mixture processed by the pelletizer 50 is processed by the vibrator to screen the mixture particles within a certain particle size range (e.g., the diameter of the mixture particles is 3-5 mm, and the length is 5-8 mm). Of course, if the screened particle size range is not within the range, it can be returned to the pelletizer 50 for re-pelletization.
[0078] In this embodiment, the setting temperature of the high temperature carbonization furnace is between 950-3500°C. Further, preferably 950-3000°C; further, preferably 1000-2800°C; further, preferably 1000-2500°C; further, preferably 1000-2200°C; further, preferably 1000-2000°C; further, preferably 1000-1800°C; further, preferably 1000-1500°C; further, preferably 1000-1400°C; further, preferably 1000-1200°C; further, preferably 1000-1100°C. The pelletized mixture particles are subjected to high temperature carbonization and sintering treatment into powder by the high temperature carbonization furnace.
[0079] In actual application, the powdered finished product can be made into any desired product shape, or used with other auxiliary materials, such as coated on the substrate described below to make a pole piece, etc., but it is not limited to the above usage scenarios.
[0080] like Figure 2 As shown, the present application also proposes a method for preparing a silicon-carbon composite negative electrode material, the preparation method comprising the following steps:
[0081] Step S1, adding asphalt and silicon powder in a certain proportion and performing a preliminary mixing process;
[0082] Step S2, remixing the mixture;
[0083] Step S3, pelletizing the remixed mixture;
[0084] Step S4, subjecting the mixture after the cutting process to high-temperature carbonization to obtain a silicon-carbon composite negative electrode material.
[0085] Among them, before the initial mixing process, that is, before step S1, a feeding process is also included, and the feeding process adopts one of a weight-loss feeder, a high-speed mixer and an internal mixer for feeding. Of course, other methods can also be used for feeding, such as using an atomizing sprayer to continue atomizing and spraying feeding, and a high-speed mixed flow homogenizing device can also be used for feeding, and an ultrasonic oscillator can also be used for feeding. The above-mentioned feeding methods are only listed as examples and do not limit the scope of protection of this application.
[0086] The above-mentioned feeding process is also equipped with a plurality of feeding bins 11, which are used to add asphalt, silicon powder, tin powder or boron powder, etc.
[0087] Among them, in this embodiment, in order to obtain a better silicon-carbon composite effect and to suppress the volume expansion of silicon to a certain extent, the mass percentage of the silicon powder and the asphalt is preferably between 5-10%, further, preferably 5-9%; further, preferably 5-8%; further, preferably 5-7%; further, preferably 5-6%.
[0088] Furthermore, when the asphalt and silicon powder are added as above, tin powder can also be added through one of the feeding bins 11, and the mass percentage of the tin powder to the silicon powder is 10-20%; further, preferably 11-19%; further, preferably 12-18%; further, preferably 13-17%; further, preferably 14-15%.
[0089] Furthermore, in the process of adding asphalt and silicon powder, or in the process of adding asphalt, silicon powder and tin powder, boron powder can also be added through one of the feeding bins 11, and the mass percentage of the boron powder to the silicon powder is 1-2%; further, preferably 1-1.5%.
[0090] In order to further promote the dispersion of the material and avoid excessive oxidation of the silicon powder, a surface coupling agent may be added through one of the feeding bins 11 .
[0091] In the above preparation method, the initial mixing process includes: using one of a twin-screw extruder, a single-screw extruder, and a reciprocating worm extruder for co-mixing and extrusion. The above mixing process is carried out by extrusion, so that the mixing between the mixtures is more uniform and the dispersion degree is higher.
[0092] The process of step S2 includes: remixing the mixture by using a static mixer 20. The static mixer 20 uses a mixing unit fixed in the pipe to change the flow state of the mixture in the pipe, so that two or more fluids are cut, sheared, rotated and remixed, so as to achieve the purpose of good dispersion and sufficient mixing between the fluids.
[0093] The turbulence blending process is further included before the pelletizing process, and the mixture is homogenized and dispersed by the turbulence blending process.
[0094] The turbulent blending process uses the turbulator for turbulent blending, wherein the turbulator includes a multi-layered hole plate, and the holes on each layer of the hole plate are arranged in a non-uniform and disordered state. In this embodiment, the shape of the holes on the hole plate is not limited, and can be one or more of circular holes, elliptical holes, square holes, petal-shaped holes, etc. Of course, for the convenience of processing and manufacturing, holes of the same shape with different aperture sizes can also be used, wherein, in order to obtain a better homogenization and dispersion effect, the holes with different aperture sizes are arranged in a non-uniform, disordered or irregular manner.
[0095] Preferably, the holes of the upper and lower perforated plates are staggered with each other, and smaller holes are formed by superposition of the upper and lower perforated plates to further enhance the homogenization and dispersion effect.
[0096] Furthermore, the number of layers of the perforated plates can be appropriately increased or decreased according to actual usage. Of course, if the number of perforated plates is greater, the homogenization and dispersion effect of the mixture may be better, but the energy consumption will increase to a certain extent.
[0097] In this embodiment, the pore size range of the hole plate is preferably between 5μm-8mm; of course, due to the superposition of multiple layers of hole plates and partial overlap of upper and lower holes during actual use, the actual effective range of pore size will be smaller than the above numerical range.
[0098] Furthermore, the above preparation method further includes a cooling treatment, wherein the mixture is cooled after the remixing treatment, wherein the cooling treatment includes water cooling treatment using a water tank 30 or air cooling treatment.
[0099] Furthermore, the above-mentioned preparation method also includes a drying process. After the mixture is cooled by the above-mentioned water, the moisture on the surface of the mixture is dried. In this step, a drying machine 40 can be used for the drying process.
[0100] In this embodiment, the mixture after pelletizing is cylindrical particles. Further, the diameter of the mixture particles is 3-5 mm and the length is 5-8 mm. The data range listed above is a preferred range. Of course, there may be mixture particles that are not within the preferred range during the pelletizing process. Therefore, this embodiment further screens and selects through the vibration screen 60 described below.
[0101] The mixture after the pelletizing process is screened by the vibrating screen 60 to screen the mixture particles within a certain particle size range (e.g., the diameter of the mixture particles is 3-5 mm and the length is 5-8 mm). Of course, if the screened particle size range is not within the range, it can be returned to the pelletizer 50 for re-pelletizing.
[0102] In this embodiment, the powdered silicon-carbon composite negative electrode material is obtained after the high-temperature carbonization treatment, wherein the setting temperature of the high-temperature carbonization treatment is referred to above and will not be repeated here. In actual application, the powdered finished product can be made into any desired product shape, or used with other auxiliary materials, such as coated on the substrate described below to make a pole piece, etc., but it is not limited to the above-mentioned usage scenarios.
[0103] This embodiment also proposes a silicon-carbon composite negative electrode material, which is obtained by the above-mentioned preparation method. The specific preparation method is shown above and will not be repeated here.
[0104] Among them, Figure 3 As shown, the capacitance change curve of the silicon-carbon composite negative electrode material in the charge and discharge process of this embodiment is obtained by converting the data to obtain the charge and discharge efficiency and other data information of the silicon-carbon composite negative electrode material, wherein the silicon-carbon composite material adopts the case where the mass percentage of silicon powder and asphalt is 5%.
[0105] Table 1 Capacitance variation of silicon-carbon composite negative electrode materials during charge and discharge
[0106] Cycle number Discharge specific capacity (mAh / g) Charge specific capacity (mAh / g) Charge and discharge efficiency (%) 1 970 820 84.5% 2 871 853 97.9%
[0107] It can be seen from Table 1 above that based on the above discharge specific capacity and charge specific capacity, the reversible specific capacity of the silicon-carbon composite negative electrode material of this embodiment is ≥820mAh / g, and the charge and discharge efficiency is ≥84.5%. In addition, the dispersed silicon-carbon composite negative electrode material obtained by the above preparation method improves the conductivity and increases the capacity and charge and discharge capacity of the negative electrode material.
[0108] The present application also proposes an application of a silicon-carbon composite negative electrode material, including the application of the silicon-carbon composite negative electrode material obtained by the above-mentioned preparation method in a negative electrode plate.
[0109] Furthermore, the above silicon-carbon composite negative electrode material is used in the negative electrode plate of a lithium battery.
[0110] Specifically, the silicon-carbon composite negative electrode material can be evenly coated on the surface of a substrate to obtain a pole piece, and then button batteries and the like can be assembled.
[0111] The reversible specific capacity of the silicon-carbon composite negative electrode material of the present application is greater than 820mAh / g, and the first charge and discharge efficiency is greater than 84.5%, which effectively reduces the volume expansion of silicon and maintains the high conductivity of the silicon-carbon composite negative electrode material, greatly improving the material cycle performance; the silicon-carbon composite negative electrode material of the present application has the characteristics of high capacity, long cycle life and high conductivity; the preparation process of the present application is simple and easy to control, and is suitable for industrial production. Therefore, the present application has broad market application prospects.
[0112] The above embodiments are only used to illustrate the technical solution of the present application but not to limit it. The present application is described in detail with reference to the preferred embodiments. It should be understood by those skilled in the art that the technical solution of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application, and should be included in the scope of the claims of the present application.
Claims
1. A silicon-carbon composite negative electrode material preparation system, characterized in that: include: Mixer, add silica powder and asphalt in a certain proportion and mix them initially; Static mixer, the mixture after the initial mixing enters the static mixer for further mixing; A turbulator, the turbulator is arranged at the outlet end of the static mixer, the turbulator includes a multi-layered hole plate, and the mixture treated by the static mixer is again subjected to a turbulator for homogenization and dispersion treatment; A water tank, wherein the water tank is arranged at the outlet end of the static flow mixer, and the mixture processed by the static flow mixer enters the water tank for cooling; A blow dryer, which is arranged at the outlet of the water tank, and after the mixture is cooled in the water tank, it enters the blow dryer to dry the moisture on its surface; A pelletizer, wherein the mixture mixed by the static mixer enters the pelletizer for pelletizing and crushing; A vibrating screen, wherein the vibrating screen is arranged at the outlet end of the pelletizer, and the mixture processed by the pelletizer is processed by a vibrator and then screened for particles of the mixture within a certain particle size range; and a high-temperature carbonization furnace. After the granulation and crushing treatment, the mixture enters the high-temperature carbonization furnace for high-temperature carbonization treatment to obtain a powdered silicon-carbon composite negative electrode material.
2. The preparation system according to claim 1, characterized in that: The holes on each layer of the hole-type plate are arranged in a non-uniform and disordered state.
3. The preparation system according to claim 2, characterized in that: The aperture of the hole plate ranges from 5 μm to 8 mm.
4. The preparation system according to any one of claims 1 to 3, characterized in that: The mixture particles are cylindrical particles.
5. The preparation system according to any one of claims 1 to 3, characterized in that: The diameter of the mixture particles is 3-5 nm and the length is 5-8 nm.
6. The preparation system according to claim 1, characterized in that: It also includes a feeder, in which at least two feeding bins are arranged, and the silicon powder and the asphalt enter the mixer through the corresponding feeding bins for initial mixing.
7. The preparation system according to claim 6, characterized in that: The feeder includes one of a loss-in-weight feeder, a high-speed mixer and an internal mixer.
8. The preparation system according to claim 6, characterized in that: One of the feeding bins is used to add tin powder, wherein the mass percentage of the tin powder to the silicon powder is 10-20%.
9. The preparation system according to claim 6, 7 or 8, characterized in that: Boron powder is added into one of the feeding bins, and the mass percentage of the boron powder to the silicon powder is 1-2%.
10. The preparation system according to claim 6, 7 or 8, characterized in that: One of the feed bins is used to add the surface coupling agent.
11. The preparation system according to claim 1 or 2 or 3 or 6 or 7 or 8, characterized in that: The mass percentage of the silicon powder and the asphalt is between 5-10%.
12. The preparation system according to claim 1 or 2 or 3 or 6 or 7 or 8, characterized in that: The mixer includes one of a twin-screw extruder, a single-screw extruder, and a reciprocating-screw extruder.
13. A method for preparing a silicon-carbon composite negative electrode material preparation system according to any one of claims 1 to 12, characterized in that: The preparation method comprises the following steps: Add asphalt and silica fume in a certain proportion and perform initial mixing; remixing the above mixture; Turbulent blending treatment, homogenizing and dispersing the mixture by turbulent blending treatment; Cooling treatment, including water cooling treatment using water tanks; Drying treatment, after the water cooling treatment, drying the water on the surface of the mixture; The remixed mixture is pelletized; Vibration screening treatment, the mixture after the pelletizing treatment is subjected to vibration screening treatment to screen the mixture particles within a certain particle size range; After high-temperature carbonization treatment, a silicon-carbon composite negative electrode material is obtained.
14. The preparation method according to claim 13, characterized in that: A feeding process is also included before the primary mixing process, and the feeding process is performed by using one of a loss-in-weight feeder, a high-speed mixer and an internal mixer.
15. The preparation method according to claim 14, characterized in that: The feeding process further includes adding tin powder through one of the feeding bins, wherein the mass percentage of the tin powder to the silicon powder is 10-20%.
16. The preparation method according to claim 14 or 15, characterized in that: The feeding process further includes adding boron powder through one of the feeding bins, wherein the mass percentage of the boron powder to the silicon powder is 1-2%.
17. The preparation method according to claim 14 or 15, characterized in that: The feeding process also includes adding a surface coupling agent through one of the feeding bins.
18. The preparation method according to claim 13, 14 or 15, characterized in that: The mass percentage of the silicon powder and the asphalt is between 5-10%.
19. The preparation method according to claim 13, characterized in that: The initial mixing process includes: using one of a twin-screw extruder, a single-screw extruder, and a reciprocating worm extruder to perform a blending extrusion process.
20. The preparation method according to claim 13 or 14 or 15 or 19, characterized in that: The mixture after pelletizing is cylindrical particles.
21. The preparation method according to claim 20, characterized in that: The cylindrical particles have a diameter of 3-5 nm and a length of 5-8 nm.
22. A silicon-carbon composite negative electrode material, characterized in that: The method is obtained by the preparation method according to any one of claims 13 to 21.
23. An application of a silicon-carbon composite negative electrode material, characterized in that: include: Use of the silicon-carbon composite negative electrode material obtained by the preparation method according to any one of claims 13 to 21 in a negative electrode sheet.
24. The use of the silicon-carbon composite negative electrode material according to claim 23, characterized in that: The silicon-carbon composite negative electrode material is evenly coated on the surface of the substrate to obtain a pole piece.
Citation Information
Patent Citations
Silicon-carbon composite negative electrode material preparation system
CN212033167U